Estimation on frequency characteristics of a photodiode determined by the motion of charge carriers in the region of volume charge on the surface generation of carriers - Danilyuk, A.I.; Dobrovolskiy, Yu.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
We have estimated the frequency characteristics of a photodiode determined
by the motion of charge carriers in the space-charge region on the surface generation of
carriers in two extreme cases of unalloyed and evenly alloyed semiconductors. The
expressions allowing the comparison of photodiodes with different constructions have
been obtained.